Recipient school environment care character adiwiyata grace in pemalang district - Syauqi, ikhwan Fadli; Pramono, Suwito Eko; Lestari, Puji (JESS (Journal of Educational Social Studies), 2023)
Environmental damage is a troubling problem for humans. The purpose of this research is to find out the application of the character of caring for school environment, implications of education caring for school sustainability, and impact of a clean and green environment. The method used was qualitative. The results of this study indicate that the application of character of caring for the environment at schools receiving the Adiwiyata award in Pemalang Regency, namely greening, agriculture, greenhouses, planting plants for family medicine, school health businesses, composting, recycling, waste banks, canteens, bulletin boards, school cleanliness, enforcement discipline, facilities and infrastructure, documentation. Implications of implementing school care: school curriculum based on the environment, extracurricular activities, and participatory activities, according to the school's vision and mission. The impact of a clean environment: the character of students who are religious, disciplined, responsible, and caring for others, students and teachers comply with school rules, and instil a caring attitude towards the school environment. With an understanding of the Adiwiyata program, it is hoped that it can provide information for schools to improve the quality of education with the methods used in learning activities related to the application of the character of caring for the school environment.